FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ISPA PADA BALITA DI PUSKESMAS SEKIP PALEMBANG TAHUN 2013 - Rini Mayasari Rini Mayasari (STIKes Budi Mulia Sriwijaya, 2014)
ABSTRACT [World Health Organization (WHO) in 2007 stated that there were 1.8 million under-five deaths due to Acute Respiratory Infections (ARI) in dunia.Yang caused by factors including toddler age, birth weight, immunization status and nutritional status. the purpose of this study is known factors associated with the incidence of respiratory infection in infants in Palembang Sekip Health Center in 2013. This study uses the Analytic Survey Cross sectional approach in this study were all toddlers (1 year - 5 years) who went to a health center Sekip IMCI in 2013. Sampling using simple random sampling, amounting to 150 people. Data analysis was done using univariate and bivariate statistical Chi-Square test with significance level α = 0.05. Univariate analysis of the results obtained from respondents who had ARI 81 (54.0%) and are not ARI 69 (46.0%), respondents who were high risk 90 (60.0%), respondents whose birth weight high risk 93 (62.0%), incomplete immunization status of 82 (54.7%), and good nutritional status of respondents 83 (55.3%). From bivariate analysis using chi-square test can be seen that there is a significant relationship between age infants with ARI incidence in Sekip Health Center Palembang, with P Value = 0.021 <α = 0.05. Incidence of birth weight with ARI in Palembang Sekip health center, with p Value = 0.005 <α = 0.05. Immunization status with the incidence of ARI P Value = 0.026 <α = 0.05. Nutritional status with ARI incidence P Value = 0.002 <α = 0.05. From the results of this study, health workers can improve health care of infants and toddlers and more often to conduct information about ARI. ABSTRAK World Health Organization (WHO) tahun 2007 menyatakan bahwa terdapat 1,8 juta kematian balita karena Infeksi Saluran Pernapasan Akut (ISPA) di dunia.Yang di sebabkan oleh factor-faktor di antaranya umur balita,berat badan lahir,status imunisasi dan status gizi.Tujuan penelitian ini adalah diketahuinya faktor-faktor yang berhubungan dengan kejadian ISPA pada balita di Puskesmas Sekip Palembang Tahun 2013. Penelitian ini menggunakan metode Survey Analitik dengan pendekatan Cross Sectional.Populasi pada penelitian ini adalah seluruh balita yang(1 tahun - 5 tahun) yang berobat ke MTBS di Puskesmas Sekip pada tahun 2013. Pengambilan sampel menggunakan teknik simple random sampling yang berjumlah 150 orang. Analisa data dilakukan secara univariat dan bivariat dengan uji statistik Chi-Square dengan tingkat kemaknaan α = 0,05. Dari analisis univariat didapatkan hasil responden yang mengalami ISPA 81 (54,0%) dan yang tidak ISPA 69 (46,0%), responden yang berumur resiko tinggi 90 (60,0%), responden yang berat badan lahir resiko tinggi 93 (62,0%), status imunisasi lengkap 82 (54,7%), serta responden yang status gizi baik 83 (55,3%). Dari analisis bivariat dengan menggunakan uji chi-square dapat dilihat bahwa ada hubungan bermakna antara umur balita dengan kejadian ISPA di Puskesmas Sekip Palembang, dengan p Value = 0,021 < α = 0,05.Berat badan lahir dengan kejadian ISPA di Puskesmas Sekip Palembang, dengan p Value = 0,005 < α = 0,05. Status imunisasi dengan kejadian ISPA p Value = 0,026 < α = 0,05.Status gizi dengan kejadian ISPA p Value = 0,002 < α = 0,05. Dari hasil penelitian ini, petugas kesehatan dapat meningkatkan pelayanan kesehatan bayi dan balita serta lebih sering untuk melaksanakan penyuluhan tentang ISPA.